2013
DOI: 10.1007/s13197-013-1081-0
|View full text |Cite
|
Sign up to set email alerts
|

Application of foam-mat drying with egg white for carrageenan: drying rate and product quality aspects

Abstract: Drying is a significant step in the production of carrageenan. However, current drying process still deals with too long drying time and carrageenan quality degradation. The foam mat drying is an option to speed up drying process as well as retaining carrageenan quality. In this case, the carrageenan was mixed with egg white (albumin) as foaming agent and methyl cellulose for foam stabilizer. The foam will break the carrageenan gels and creates the porous structure resulting higher surface area for water trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 17 publications
3
47
0
1
Order By: Relevance
“…The result also showed that the increase air temperature can speed up water removal. With higher temperature, the water diffusivity increased 1,11 . Therefore, more water moved from inside to the surface of seaweed.…”
Section: The Effect Of Zeolitementioning
confidence: 99%
See 2 more Smart Citations
“…The result also showed that the increase air temperature can speed up water removal. With higher temperature, the water diffusivity increased 1,11 . Therefore, more water moved from inside to the surface of seaweed.…”
Section: The Effect Of Zeolitementioning
confidence: 99%
“…At higher temperature, the water movement from inside to the surface of seaweed increased. Then, the water evaporation can be higher 1,3,5,11 .…”
Section: The Effect Of Operational Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…The drying rate of the foamed pulp at 50°C, 60°C and 70°C was found to be 0.559, 0.782 and 1.005 g min -1 , respectively, whereas for the unfoamed pulp it was 0.351, 0.524 and 0.592 g min -1 , respectively. This was due to the increased evaporation surface in foamed pulp, which facilitated the removal of large quantity of water [48]. At the final stages of drying, the drying rate started to decrease.…”
Section: Drying Characteristics Of Muskmelon Pulpmentioning
confidence: 99%
“…In order to provide stable gas–liquid foam, high‐molecular weight polysaccharides such as xanthan gum (Muthukumaran et al, ; Salahi, Mohebbi, & Taghizadeh, ), arabic gum, starch, maltodextrin (MD) (Sramek, Schweiggert, Van Kampen, Carle, & Kohlus, ), pectins, carboxymethyl cellulose (CMC) (Branco, Kikuchi, Argandona, Moraes, & Haminiuk, ; Chaves, Barreto, Reis, & Kadam, ; Kaushal, Sharma, & Sharma, ; Wilson, Kadam, & Kaur, ), and methyl cellulose (Djaeni, Prasetyaningrum, Sasongko, Widayat, & Hii, ; Raharitsifa, Genovese, & Ratti, ) are used as foaming stabilizers, while protein‐structured components such as soy proteins (Rajkumar, Kailappan, Viswanathan, Raghavan, & Ratti, ; Sankat & Castaigne, ; Zheng, Liu, & Zhou, ), whey proteins (Sramek et al, ), casein, egg white (EW) (Abbasi & Azizpour, ; Kadam et al, ; Kandasamy, Varadharaju, Kalemullah, & Maladhi, ; Raharitsifa & Ratti, ; Wilson, Kadam, Chadha, Grewal, & Sharma, ), egg albumin (Franco, Perussello, Ellendersen, & Masson, ; Prakotmak, Soponronnarit, & Prachayawarakorn, ; Thuwapanichayanan, Prachayawarakorn, & Soponronnarit, ), and gelatin are used as foaming agents. Foaming stabilizers improve the foam stability by increasing the interfacial viscoelasticity, while foaming agents create air gaps and intramolecular hydrogen bonds in the foam.…”
Section: Introductionmentioning
confidence: 99%